2001
DOI: 10.1002/1521-3773(20011203)40:23<4496::aid-anie4496>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Permanganate-Promoted Oxidative Cyclization of 1,5-Dienes by Using Chiral Phase-Transfer Catalysis This work was supported by the EPSRC (J.F.K.) and the Royal Society (R.C.D.B.). We thank Dr. Barry Lygo (University of Nottingham) for helpful discussions, and Syngenta and Merck Sharp and Dohme for unrestricted grants.

Abstract: Up to four new stereocenters are created with control of the relative and absolute stereochemistry in a single step in the unusual phase‐transfer‐catalyzed oxidative cyclization of achiral dienes with permanganate (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…It should be noted that the stereochemistry of the permanganate-mediated cyclization allows the elegant assembly of the tetrahydrofuran-diol portion of some of these products. For example, in the synthesis of cis-solamin, 23 a threo-cis-threo mono-tetrahydrofuran acetogenin, the pivotal cyclization step of diene 11 (Scheme 11, top), derivatized with (2S)-10,2-camphorsultam, was accomplished in a 55% yield and 10:1 diastereomeric ratio under phase-transfer conditions 24 (see below), previously set up by the same authors, with ethyl acetate as solvent. This result also demonstrated that new conditions had to be devised in order to induce unbranched 1,5-dienes to cyclize in reasonable yields.…”
Section: Scheme 7 Permanganate-mediated Diastereoselective Oxidative mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the stereochemistry of the permanganate-mediated cyclization allows the elegant assembly of the tetrahydrofuran-diol portion of some of these products. For example, in the synthesis of cis-solamin, 23 a threo-cis-threo mono-tetrahydrofuran acetogenin, the pivotal cyclization step of diene 11 (Scheme 11, top), derivatized with (2S)-10,2-camphorsultam, was accomplished in a 55% yield and 10:1 diastereomeric ratio under phase-transfer conditions 24 (see below), previously set up by the same authors, with ethyl acetate as solvent. This result also demonstrated that new conditions had to be devised in order to induce unbranched 1,5-dienes to cyclize in reasonable yields.…”
Section: Scheme 7 Permanganate-mediated Diastereoselective Oxidative mentioning
confidence: 99%
“…28 The first, which was cis-stereoselective, was performed with potassium permanganate in acetone-acetic acid; the second, carried out with trifluoroacetyl perrhenate (from Re 2 O 7 -TFAA), allowed for the closure of the trans-tetrahydrofuran ring, with the anticipated stereoselectivity based on that displayed in the hydroxyl-directed oxidative cyclization of bishomoallylic alcohols with rhenium(VII) oxides. 29 Brown and Keily 24 were also able to obtain promising levels of asymmetric induction by performing the oxidative 31 The presence of a catalytic amount of water was crucial to this process, and a large amount of both potassium permanganate (25 equiv) and copper(II) sulfate pentahydrate (11 equiv) was employed. In some cases, minor amounts (8-10%) of the related d-lactones were obtained.…”
Section: Scheme 7 Permanganate-mediated Diastereoselective Oxidative mentioning
confidence: 99%
“…Previously established standard conditions using acetone–water delivered THF-diol 28a in only 18% yield. Better results were achieved when the oxidative cyclization was carried out under phase-transfer conditions [84]. Thus, the corresponding THF diols were obtained in 55% yield.…”
Section: Reviewmentioning
confidence: 99%
“…The addition of acetic acid is quite important for the reaction to proceed, and highly functionalized tetrahydrofurans are obtained in a range of 58 to 75% ee, in diastereoselective manner [35]. Another oxidative transformation using KMnO 4 with a chiral ammonium salt has been investigated.…”
Section: Asymmetric Oxygen-functionalizationmentioning
confidence: 99%